1981
DOI: 10.1002/net.3230110209
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial optimization and vehicle fleet planning: Perspectives and prospects

Abstract: As a well‐structured and costly activity that pervades industries in both the public and private sector, vehicle fleet management would appear to be a splendid candidate for model‐based planning and optimization. And yet, until recently the combinatorial intricacies of vehicle routing and of vehicle scheduling have precluded the widespread use of optimization (exact) methods for this problem class. Our discussion in this paper identifies the extent and nature of these problem complexities and draws contrasts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(27 citation statements)
references
References 92 publications
0
24
0
3
Order By: Relevance
“…The formulation was first introduced in vehicle routing by Balinski and Quandt (1964). Magnanti (1981) has shown that the vehicle flow formulation of the classical one depot vehicle routing problem may be rewritten into a formulation similar to the set partitioning problem. In the classical VRP a feasible solution should satisfy a number of constraints like: (1) a vehicle is used at most once; (2) if a vehicle arrives at a customer, it must also depart from there; (3) the load of the vehicle should not exceed its capacity; (4) subtour elimination constraints and (5) integrality of the decision variables.…”
Section: Set Partitioning Approachmentioning
confidence: 99%
“…The formulation was first introduced in vehicle routing by Balinski and Quandt (1964). Magnanti (1981) has shown that the vehicle flow formulation of the classical one depot vehicle routing problem may be rewritten into a formulation similar to the set partitioning problem. In the classical VRP a feasible solution should satisfy a number of constraints like: (1) a vehicle is used at most once; (2) if a vehicle arrives at a customer, it must also depart from there; (3) the load of the vehicle should not exceed its capacity; (4) subtour elimination constraints and (5) integrality of the decision variables.…”
Section: Set Partitioning Approachmentioning
confidence: 99%
“…Using the classification of Magnanti (1981), Laporte (1988) puts the integer programming algorithms into the following four categories:…”
Section: Classificationsmentioning
confidence: 99%
“…In the literature, Laporte and Nobert (1987) presented an extensive survey that was entirely devoted to exact methods for the VRP, where they gave a complete and detailed analysis of the state-of-the-art up to the late 1980s. Other surveys also cover exact methods, but are often more devoted to heuristic and metaheuristic methods, including those by Christofides, Mingozzi, and Toth (1979), Magnanti (1981), Bodin et al (1983), Christofides (1985), Laporte (1992), Fisher (1995, Toth and Vigo (1998), and Golden et al (1998). Bibliographies were presented by Laporte and Osman (1995) and Laporte (1997), while books include those by Golden and Assad (1988) and Toth and Vigo (2002).…”
Section: General Solution Approachesmentioning
confidence: 99%